A data-cleaning augmented Kalman filter for robust estimation of state space models - Martyna Marczak; Tommaso Proietti; Stefano Grassi (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2015)
This article presents a robust augmented Kalman filter that extends the data-cleaning filter (Masreliez and Martin, 1977) to the general state space model featuring nonstationary and regression effects. The robust filter shrinks the observations towards their one-step-ahead prediction based on the past, by bounding the effect of the information carried by a new observation according to an influence function. When maximum likelihood estimation is carried out on the replacement data, an M-type estimator is obtained. We investigate the performance of the robust AKF in two applications using as a modeling framework the basic structural time series model, a popular unobserved components model in the analysis of seasonal time series. First, a Monte Carlo experiment is conducted in order to evaluate the comparative accuracy of the proposed method for estimating the variance parameters. Second, the method is applied in a forecasting context to a large set of European trade statistics series.
urn:nbn:de:bsz:100-opus-11563
Keywords: C32; C53; C63; 330; robust filtering; augmented Kalman filter; structural time series model; additive outlier; innovation outlier